Physical activity in the post-COVID-19: AEROBICOVID project design and perspectives - Costa, Gabriel Peinado; Wiggers, Ester; Foresti, Yan Figueiredo; Sorgi, Carlos Arterio; Papoti, Marcelo; Trapé, Átila Alexandre (Medicina (Ribeirao Preto), 2022)
During the COVID-19 pandemic, several late-onset impairments have been observed, affecting the health and functionality of those involved. On the other hand, lower SARS-CoV-2 infection rates and severity of symptoms were observed in high-altitude cities. In this sense, the AEROBICOVID project was developed with the hypothesis that exercise would be an important opportunity for health improvement and that hypoxia would promote additional benefits in the recovery process. The cohort was about 84 participants with approximately 30 days since the COVID-19 symptoms recovery, 25 in the control group, and 59 divided into three moderate physical training groups. The project had good results in teaching, research, and extension, but also faced difficulties in operationalization. This experience is the basis for future proposals through an extension project at the University of São Paulo and in a Family Health Unit, besides a research project that will develop a new low-cost hypoxia technology.